Rare giant ovarian thecoma presented as atypical/incomplete Meigs' syndrome: A case image report - Anastasios Potiris; Ioannis S. Pateras; Nektarios Koufopoulos; Menelaos G. Samaras; Spyridon Topis; Maria‐Gesthimani Chousmekeridou; Athanasios Zikopoulos; Ekaterini Domali; Peter Drakakis; Sofoklis Stavros (Clinical Case Reports, 2024)
Key Clinical Message We present a 39‐centimeter thecoma with ascites and elevated Ca‐125 values which is compatible with an atypical/incomplete Meigs' syndrome. Giant ovarian masses with elevated Ca‐125 values and ascites are an alarming combination, although Gynecologists should be aware that there are also benign entities that mimic advanced stage ovarian cancer.